Environmental reconstruction and formation processes in a large Mesolithic lithic scatter at Nethermills of Crathes, Aberdeenshire, Scotland. (October 2022) - Tipping, Richard; Bates, Richard; Cameron, Alison; Clarke, Ann; Duthie, Sheila; Ewan, Lorna; Kinnaird, Tim; Mann, Bruce; Noble, Gordon; Ross, Irvine; Sabnis, Heather; Wickham-Jones, Caroline
Graphical abstract: Highlights: We reconstructed in detail the habitats of hunter-gatherer-fishers. Late Upper Palaeolithic groups spent time on active gravel bars of the River Dee in Scotland. Mesolithic groups occupied the floodplain, attracted to riverine resources. The floodplain became increasingly dry and wooded through channel incision. Abstract: The rich resources of river valleys provided a focus for much Mesolithic hunter-gatherer-fisher activities across Europe. In Scotland there is one notable concentration of lithic evidence for this, at several locations along the River Dee in Aberdeenshire, but the environmental context of these sites has, to date, been poorly understood. Here we present evidence from excavation, repeated field-walking, flint typology, geomorphological mapping, sedimentology, pollen analysis, AMS 14 C dating, OSL profiling and dating to understand the postglacial evolution of the terrace surface at the largest concentration of lithics along the River Dee, at Nethermills of Crathes. The aim was to understand in detail the environment and landscape dynamics of the site, to define whether occupation was on the active valley floor or on a terrace above the river, and whether fluvial processes had a role in site formation processes. We conclude that occupation was on a dry wooded surface, the active channel having incised below this, though to an unknown depth, and that although major floods have swept the terrace surface, the present distribution of lithics is probably largely the original distribution.